Chittagong Medical College Recommendations for MBBS Curriculum 2002 Review - Khan, Aminuddin A; Yunus, Emran Bin; Hassan, Md Mahtab Uddin; Haque, Mahmudul; Mazumder, Saroj Kumar; Chowdhury, Shahanara (Journal of Chittagong Medical College Teachers’ Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5618 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):6-11